The Stewart/Colbert effect essays on the real impacts of fake news - Amarasingam, Amarnath; McChesney, Robert W. (McFarland & Company, Inc., Publishers, 2011)
"The ten essays in this interdisciplinary collection explore the issues engendered by the popularity of entertainment news, including the role of satire in politics, the declining level of trust in traditional sources of media, the shows' cathartic or informational function, and the ways in which these shows influence public opinion"--Provided by publisher.